Іноземні консули в УCРР (1919-1922 рр.) - Матяш, І. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті висвітлено основні форми та проблеми діяльності іноземних консулів у Києві та «радянській столиці» Харкові впродовж
лютого 1919 р. — грудня 1922 р. Досліджено основні форми і методи
діяльності іноземних консульств в Українській СРР, виявлено особливості їх функціонування, з’ясовано особовий склад консульських установ і роль їх керівників у започаткуванні консульських зносин із УСРР та вплив
на формування її міжнародних зв’язків. Охарактеризовано особи іноземних консулів (В. Дубинського, М. Дж. Мір-Тагієва, К. Цагарелі, Біт Шумуна та ін.), які репрезентували в радянській Україні Азербайджан,
Вірменію, Грузію, Персію та інші країни. На підставі архівної інформації
досліджено особливості взаємодії Народного комісаріату закордонних
справ УСРР з іноземними представництвами та дії Головного політичного управління УСРР щодо реєстрації іноземних громадян. Розглянуто
нормативні акти щодо становища іноземних підданих в Українській СРР
та висвітлено роль іноземних консулів у забезпеченні контактів підданих
їхніх держав із радянськими органами. Доведено, що іноземні консули в
УСРР ставали жертвами репресивних органів. The article describes the basic forms and problems of foreign consuls’
activities in Kyiv and «Soviet capital» Kharkiv in February 1919 — December
1922. We surveyed historiography (works by Hisem O.V., Kiladze S., Kupchyk
O.V., Danylenko O.V., Netreba Y.B., Sokyrska V.V. etc.) and a wide range
of sources concerning activities of foreign missions in Ukraine. The main forms
and methods of foreign consulates’ activities in the Ukrainian SSR were
surveyed, peculiarities of their functioning were outlined, personnel of the
consular institutions and a role of their management in formation of consular
relations with the Ukrainian SSR and an influence on building its foreign
relations were determined. We characterized the personalities of the foreign
consuls who represented Azerbaijan, Armenia, Georgia, Persia and other
countries in Soviet Ukraine (Dubynskyi V., Mir-Tagiev J., Tsahareli K.,
Shumun Bit etc.). Indicated on the nationalization of foreign consulates’
buildings by the Soviet authorities. Nature of the activities of Chinese mission,
mission of Assyrian National Delegation in the RSFSR and «a Brazilian consul
earl Alberto Pirro» was also highlighted. On the basis of archival information
we investigated features of the interaction of the People’s Commissariat for
Foreign Affairs of the USSR to the foreign missions and actions of the USSR
General Political Governance corcerning registration of foreigners. It has
been shown that the foreign missions used the services of the Bureau for
Foreign Missions Services concerning providing people with food provision
and dwelling. We found differences in the organization of the consular corps in
the era of the Ukrainian State and the Ukrainian People’s Republic and the
Soviet regime. Regulations on the status of foreign nationals in the Ukrainian
SSR were considered, and the role of the foreign consuls in ensuring contacts
of the citizens of their states with the Soviet authorities was highlighted. It was
proved that foreign consuls in the Ukrainian SSR were victims of repressive
bodies.